South West Region: River Yarty, Sir Arthur's Pill - Dunderdale, J. A. L.; Morris, J. (National Rivers Authority, 1996)
This document describes methods, results and conclusions of a study to evaluate the impacts of alternative river maintenance strategies on the River Yarty and Sir Arther's Pill in the South Western Region. Its main purpose are to provide supporting information for R&D Note 456 'River Maintenance Evaluation' and to provide data which supports routines for the prioritisation and programming of river maintenance.